2001
DOI: 10.1002/joc.626
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and atmospheric circulation patterns at mid‐latitudes of Asia

Abstract: Analyses of the coupling between large-scale atmospheric patterns and modifications of regional precipitation regimes at seasonal and annual time scales in different terrain of mid-latitudes in Asia, including western Siberia, Tien Shan and Pamir mountains, and plains of middle Asia and Japanese Islands, were examined based on data from 57 and 88 hydro-climatic stations with 100 and 60 year records, respectively. For the past 100 years, a positive trend in precipitation was revealed in western Siberia, norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(218 citation statements)
references
References 22 publications
(36 reference statements)
5
211
1
1
Order By: Relevance
“…The warm surface water extends westward during the spring, leading to a lagged response in the atmosphere associated with the weakened spring Aleutian Low. Aizen et al (2001) have suggested that the NAO is one of main atmospheric circulation factors determining the climate in continental Asia, which is different from those affecting the Japanese Islands. From our studies, the evidence has showed that the winter NAO influences not only the winter Northern Hemisphere climate but also the subsequent spring climate including the North Pacific region through both North Pacific SST and Eurasian snow mechanisms.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The warm surface water extends westward during the spring, leading to a lagged response in the atmosphere associated with the weakened spring Aleutian Low. Aizen et al (2001) have suggested that the NAO is one of main atmospheric circulation factors determining the climate in continental Asia, which is different from those affecting the Japanese Islands. From our studies, the evidence has showed that the winter NAO influences not only the winter Northern Hemisphere climate but also the subsequent spring climate including the North Pacific region through both North Pacific SST and Eurasian snow mechanisms.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In particular, the positive phase of the NAO is associated with an increase in precipitation over northern Europe and a decrease in precipitation over central and southern Europe as well as North Africa (Lamb and Peppler, 1987;Hurrell, 1995). Recently, NAO-related precipitation signals in the Middle East and Asia have also been identified (Cullen and deMenocal, 2000;Aizen et al, 2001;Visbeck et al, 2001). For example, Aizen et al (2001) investigated the atmospheric circulation patterns associated with seasonal and annual precipitation anomalies in central Eurasia and Japan and showed that the NAO has an influence on the winter precipitation in these regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be deduced that a change in the amount of snowfall for these regions was mainly the result of changes in the amount of precipitation based on the above statements. With increases in precipitation in the main precipitation seasons (Hewitt, 2005;Yao and others, 2012;Kapnick and others, 2014;Zhang and others, 2017), such as in winter in the Karakoram, and in the ablation season in the Muztag Ata region, this leads to increases in snowfall and further decreases in melt energy in the ablation season due to increasing albedo under warming and and others, 2016), the mean air temperature was higher during 2001-2012than 1970(Zhang and others, 2017. This means that a greater mass loss occurred during the period of 2001-2012 than during 1970-2000 for these regions, which was in contrast with the observed regional glacier changes.…”
Section: Comparing Muztag Ata No15 Glacier With Other Glaciers On Thmentioning
confidence: 98%
“…), about 50 km east of Son Kol, the average annual precipitation amounts to ~400 mm (Williams and Konovalov, 2008), it is clearly higher at the lake itself (500-600 mm; Academy of Science of the Kyrgyz SSR, 1987). Most of the precipitation in the area occurs as convective rainfall during summer, driven by moist westerly air masses (Aizen et al, 2001), whereas only about 20% fall between November and March (Academy of Science of the Kyrgyz SSR, 1987) because of the blocking of the Westerlies by the Siberian Anticyclone in winter.…”
Section: Study Sitementioning
confidence: 99%